Right of women to mahr (dower) under Islamic Law and Malaysian family law: some suggestions for reform - Abdul Hak, Nora (Serials Publications, 2012)
Mahr (dower) is considered as an essential part of a Muslim marriage. It is given by a man to his wife as a matter of her right as it has been mentioned in the Qur’an and Hadith of the Prophet Muhammad s.a.w. In Islam, mahr is a marriage gift from the man to his wife and becomes her exclusive property. It is also given as a mark of respect for her. If the mahr is not paid during the marriage, the right to mahr remains even after divorce except in certain circumstances. The article will deliberate the right of a woman to mahr (dower) in Islamic law. In this article, the differences of views of some Muslims jurists pertaining to this matter will be deliberated. Legal provisions and the practice of the Malaysian courts in entertaining this right of a woman will be the focus of the article. Thus, cases decided at the Shariah Courts relating to the claim of mahr (dower) will be referred to study the practice of it in Malaysia as well as its problems. Comparison with other jurisdictions on the practice of mahr (dower) will be highlighted especially the practice in India. It is hoped that by analysing the current the legal provisions on mahr and its practice, suggestions and recommendations can be made to further improve this area of law. Hence, the right of Muslim women to mahr (dower) as enshrined in the Qur’an will be preserved.